Formulating Knowledge-Based Cloud Identity Selection. Issue 3 (4th May 2021) - Cusack, Brian; Ghazizadeh, Eghbal
ABSTRACT: Cloud identity is critical in the adoption of cloud computing. Identity providers provide identity as a service for the cloud customers to facilitate the access to resources, but often provide no informed choice of the supply arrangements. The cloud customer requires a say in the elements of service that impact their expectations and quality of service – particularly in relation to the security and privacy of information. In this paper, we provide a novel software solution for addressing the problem. It allows for selecting a most trustable provider, in terms of security, privacy, risk, and standards. The application architecture uses a trust evaluation model as a third-party agency for informing the service user of evidence for and against a choice. A case study and application build demonstrate the feasibility and usefulness of the proposed method in a real cloud environment.